Neue Sachlichkeit 1918-33 : unity and diversity of an art movement - Plumb, Steve (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft, 2006)
Neue Sachlichkeit is thought by many to have too many diverse elements to be a unified movement. Originally divided by G.F. Hartlaub into two 'wings', Neue Sachlichkeit has since been broken down by critics into more groups, sometimes with opposing styles or regional influences. However, the importance of these divisions has rarely been explored in depth. Unlike previous surveys, which accept Neue Sachlichkeit as a divided entity, this book shows for the first time that in spite of its divisions, it may still be regarded as a unified, coherent movement. While different artists may have sought.